(untitled) (Research, Society and Development, 2021)
Objective: To evaluate knowledge of undergraduates and qualified dentists from a Brazilian Dental School in treating Dentine Hypersensitivity (DH). Methodology: Data obtained from a 22-item questionnaire were analysed and arranged in distribution figures. Results: Of 100 respondents, 66.3% indicated that up to 25% of their patients had DH; 41.7%, that the duration of discomfort was up to eight weeks; 78.4%, that they examined a patient with DH within the last two-four weeks; and 70.4%, that this was done after the patient initiated the conversation on DH. Most of participants responded DH affects patients’ quality of life, and its aetiology was attrition, exposed dentine, occlusal interference, gingival recession or abrasion. The most common ways to diagnose DH were sensitivity history analysis, clinical examination, clinical testing and probing; and conflicting conditions were fractured restoration, bleaching sensitivity, marginal leakage, chipped tooth and periodontal disease. Furthermore, 82.5% and 78.7% of respondents indicated they were confident in diagnosing DH and providing advice to patients, but only 38.8% identified hydrodynamic theory as its underlying mechanism. To evaluate pain from DH they considered self-assessment, dental examination, dietary analysis and thermal assessment; and as recommendations, the use of desensitizing dentifrices, education on toothbrushing, in-office application of desensitizing products, and restorations. Conclusion: There is still confusion concerning the aetiology, the diagnosis and the subsequent management of DH, and both students and qualified dentists need better education.